METHOD OF THE STATISTICAL DIAGNOSTIC OF RELIABILITY OF SHIPS’ EQUIPMENT - Tykhonov, Illya (Proceedings of National Aviation University (archive), 2018)
Purpose: The purpose of this article is to present the method of the statistical diagnostic of ship onboard electronic equipment reliability. with using of probabilistic model of stream of refuses on the Neyman-Pirson’s plausibility criteria. Method: The article describes the method of account these criteria which allow to increase a control level on the state of reliability of ship onboard electronic equipment with using of the statistical diagnostic. Results: On the basis of the analysis conducting received in relation to the level of reliability of ship equipment made decision concerning to possible declining of equipment reliability level and terms and volume of his technical service. Discussion: The proposed method is the methodological basis for search of extremums of Neyman-Pirson’s criteria of the supervisions terms and permit to provide the diagnostic of ship onboard equipment reliability.